Policy challenges faced by low-income CIS economies - Marek Dabrowski (Center for Social and Economic Research (CASE), 2008)
In the 1990s, the CIS region experienced a painful transformation following the collapse of the USSR and the command economy. For the less developed republics of the former USSR, this process was even more dramatic as they lost subsidies from the Union's budget and some of them suffered devastating conflicts. In the 2000s, after overcoming the adaptation output decline and the consequences of the 1998-1999 financial crises, these economies started to grow rapidly, reducing poverty and macroeconomic imbalances. However, their future growth prospects are increasingly vulnerable due to their strong dependence on commodity exports, a poor business and investment climate, endemic corruption and weak governance. Quite recently, fighting high inflation has returned to the policy agenda. The modernization and diversification of the low-income CIS economies requires further market and institutional reforms aimed at overcoming the Soviet legacy of a repressive and inefficient state. The international community can help by resolving regional conflicts, assisting with trade and economic integration, and offering well-targeted development assistance.
Keywords: P24; P33; P36; 330; Commonwealth of Independent States; transition; low income countries; Southern Caucasus; Central Asia; trade; investment climate; Volkswirtschaft; Investitionsklima; Wirtschaftsintegration; Politische Reform; Wirtschaftspolitik; Entwicklungshilfe; Entwicklungsländer; GUS-Staaten